New records of herbivory of Leucothyreus MacLeay, 1819 (Coleoptera: Scarabaeidae: Geniatini) on Cecropia Loefl. (Urticaceae) - Aguiar, Daniel P. P.; Bento, Matheus (Entomological Communications, 2024)
Species in the genus Cecropia Loefl. (Urticaceae) are important food sources for a handful of species belonging to the insect orders Orthoptera (grasshoppers), Lepidoptera (caterpillars), Hymenoptera (leafcutter ants), and Coleoptera (beetles). Among the leaf chafer beetles, specimens of the scarab genus Leucothyreus MacLeay, 1819 (Scarabaeidae: Geniatini) have been barely recorded as defoliators of Cecropia spp., and information about the identity of the involved plant and beetle species is scarce and imprecise. The present paper records for the first time the incidence of two species of Leucothyreus on four species of Cecropia in Central Amazon (Brazil), with short behavioral notes regarding their feeding habits.